The Effect Of Brand Trust On Purchase Intention For The Ampo Beverage Brand in Jember - Swastika, Melur Tri; Hapsari, Indria Dwi (Journal of Digital Business Innovation, 2023)
The purpose of this study is to determine the influence of brand trust on purchase intention for AMPO drinking water in Jember. The number of samples in this study was 200 respondents using saturated samples. The analysis technique used is SEM using WarpPLS 8.0. The research method used in this research is outer model analysis and inner model analysis. The results of data analysis show that there is a significant influence of brand trust on purchase intention for AMPO drinking water in Jember with a contribution level of 25.4% and the remaining 74.6% is influenced by other factors not included in the research.